Critical Analysis of The Impact of Multiculturalism in Modern Islamic Education Learning Methods - Zaenudin, Ahmad; Fitri, Laely Mahfurotul; Abidin, Zaenal (Kirana Publisher (KNPub), 2025)
The phenomenon of globalization and increasingly intense cultural migration flows bring new challenges in the world of education, including in modern Islamic education. The cultural diversity that grows in the school environment demands inclusive and adaptive learning methods. However, in reality, many Islamic educational institutions have not been fully able to integrate the values of multiculturalism constructively into learning methods, thus creating a gap between the reality of implementation and the ideal of Islamic education that is rahmatan lil 'alamin. This study aims to critically analyze three main focuses: (1) the influence of multiculturalism on the choice of learning methods, (2) its impact on teacher-student interaction, and (3) the extent to which learning methods are able to accommodate multicultural values without violating the principles of Islamic teachings. The approach used is qualitative-descriptive with a case study method. Data were collected through in-depth interviews, observations, and documentation from three modern Islamic schools in urban areas. Data analysis was carried out by reduction, categorization, and thematic interpretation techniques. The results of the study show that the integration of multicultural values in learning methods is still partial and highly dependent on the readiness of teachers. In conclusion, a more culturally conscious pedagogical strategy is needed to bridge Islamic values with a plurality of students